Identification, Expression Patterns, and Functional Characterization of Chemosensory Proteins in Dendroctonus armandi (Coleoptera: Curculionidae: Scolytinae) - Li, Zhumei; Dai, Lulu; Chu, Honglong; Fu, Danyang; Sun, Yaya; Chen, Hui (Frontiers in Physiology, 2018)
The Chinese white pine beetle, Dendroctonus armandi Tsai and Li (Coleoptera: Curculionidae: Scolytinae), is a serious pest of coniferous forests in China. Thus, there is considerable interest in developing eco-friendly pest-control methods, with the use of semiochemicals as a distinct possibility. Olfaction is extremely important for fitness of D. armandi because it is the primary mechanism through which the insect locates hosts and mates. Thus, here we characterized nine full-length genes encoding chemosensory proteins (CSPs) from D. armandi. The genes were ubiquitously and multiply expressed across different developmental stages and adult tissues, indicating various roles in developmental metamorphosis, olfaction, and gustation. Ligand-binding assays implied that DarmCSP2 may be the carrier of D. armandi pheromones and various plant host volatiles. These volatiles were identified through RNA interference of DarmCSP2 as: (+)-α-pinene, (+)-β-pinene, (-)-β-pinene, (+)-camphene, (+)-3-carene, and myrcene. The systematic chemosensory functional analysis of DarmCSP2 in this study clarified the molecular mechanisms underlying D. armandi olfaction and provided a theoretical foundation for eco-friendly pest control.